2012
DOI: 10.1111/apa.12093
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of overweight prevalence among 5–6‐year‐old children according to socio‐economic status

Abstract: Overweight prevalence has decreased between 2004 and 2011 in 5-6-year-old children from Bordeaux. However, the gap between low and non-low-SES areas has persisted during these years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
(37 reference statements)
2
4
0
Order By: Relevance
“…Other European studies have found increasing differences in the prevalence of overweight and obesity by socioeconomic status as well. However, consistent significant socioeconomic differences in the overweight prevalence across school years were only reported in France [ 20 ], whereas in Sweden and England significant social differences were only found in few years [ 8 , 9 ], just as in our study.…”
Section: Discussionsupporting
confidence: 85%
“…Other European studies have found increasing differences in the prevalence of overweight and obesity by socioeconomic status as well. However, consistent significant socioeconomic differences in the overweight prevalence across school years were only reported in France [ 20 ], whereas in Sweden and England significant social differences were only found in few years [ 8 , 9 ], just as in our study.…”
Section: Discussionsupporting
confidence: 85%
“…In France, separate cross-sectional studies have demonstrated an inverse relation between socioeconomic position and OW at both 5-6 years [27][28][29] and at 2 years. 30 Given this background, we hypothesised that this inverse relation with socioeconomic position was likely to be apparent by 2 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…This programme included widespread claims to promote healthy dietary habits, multiple school interventions and changes in the built environment to promote physical activity. Numerous healthcare professionals involved in school‐based obesity prevention programmes also suggest that their actions have had a positive impact . However, better childhood obesity prevention does not seem to explain the low rates of overweight and obesity in French children.…”
mentioning
confidence: 99%
“…In addition, some French studies had showed that programmes that aimed to prevent childhood obesity had proved successful . However, there could be some obvious biases that explain why the authors of these studies assumed that their programme was working.…”
mentioning
confidence: 99%
See 1 more Smart Citation